Hubungan Pengetahuan Ibu Tentang Teknik Menyusui Yang Benar Dengan Kejadian Puting Lecet Pada Ibu Nifas Di Bpm Siti Sujalmi, Jatinom, Klaten - Astri Wahyuningsih; Endang Wahyuningsih (Stikes Muhammadiyah Klaten, 2020)
Breastfeeding techniques are good not only for first-time mothers, but also for mothers who have breastfed their babies. Thus mothers need to learn to interact with their babies in order to be successful in providing the best for their babies. The results obtained from a preliminary study of 7 postpartum mothers, there were 4 postpartum mothers who experienced blistered nipples and 3 postpartum mothers who did not experience sore nipples due to applying the correct breastfeeding technique. This study was to determine the relationship between mother's knowledge about the correct breastfeeding technique and the incidence of blisters in postpartum mothers at BPM Siti Sujalmi, Jatinom, Klaten. This research method used analytic descriptive design with a cross sectional approach. The sampling technique in this study used a total sampling technique with a total sample of 51 postpartum mothers. The results showed the p value 0.035 <0.05. This shows that there is a relationship between mother's knowledge of correct breastfeeding techniques and the incidence of nipple blisters in postpartum mothers at BPM Siti Sujalmi, Jatinom, Klaten. The conclusion of this study is that there is a relationship between mother's knowledge of correct breastfeeding techniques and the incidence of blistered nipples in postpartum mothers. Suggestions for postpartum mothers can increase their knowledge of correct breastfeeding techniques by paying attention to the attachment and position of the baby while breastfeeding so that the nipple is not chafed.